INNOVATIVE WAYS TO IMPROVE THE PROFESSIONAL SKILLS OF FUTURE PRIMARY SCHOOL TEACHERS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article looks at creative ways to help aspiring primary school teachers develop their professional abilities. It is crucial to give aspiring teachers skills that are both applicable and flexible enough to work in a variety of classroom settings as educational paradigms change. This research examines successful tactics for teacher education programs by examining collaborative learning, technological integration, and experiential training. The essay also emphasizes the value of mentoring and ongoing professional development in creating a growth-oriented culture among future educators. The results indicate that teacher preparation programs may greatly increase the competency and self-assurance of aspiring primary educators by using new pedagogical techniques.